Etude de l’activité antibactérienne des huiles essentielles de Thymus vulgaris de Nedroma (Algérie) sur les bactéries responsables des infections post-opératoires au centre Hospitalier Régionale Amissa Bongo de Franceville - ENGANDJIS OTHAS, Aurel Gaumez (My University, 2017)
Currently, there is a global public health problem. These include the long-standing appearance of resistant bacterial strains involved in some post-operative infections. This work is intended as a contribution to test the effect of antibiotics used in hospitals and to enhance the essential oil of Thymus vulgaris from the Nedroma Wilaya region of Tlemcen (Algeria) on the germs responsible for post-operative infections. Samples collected from Pus and Compress on wounds show a high prevalence of Grampositive bacteria such as Staphylococcus aureus from pus specimens and Enterobacteriaceae such as Escherichia coli, Klebsiella pneumoniae ssp pneumoniae. The antibiotic tests carried out showed a very high resistance rate of about 8 out of 16 antibiotics tested in strains such as Pseudomonas aeruginosa, Escherichia Coli, Klebsiella pneumoniae ssp pneumoniae, Staphylococcus aureus with zero diameters for several strains Of S. aureus. The antibacterial activity demonstrated by the antibio-aromatogram method, showed that the essential oil of Thymus vulgaris from the Nedroma Wilaya region of Tlemcen (Algeria) showed a significant inhibitory effect on certain bacterial strains with profiles of weak resistance (Proteus mirabilis, E. coli ATCC25922). Medium (Citrobacter freundii, Shigella group) and Fort (Staphylococcus aureus and Klebsiella pneumoniae ssp pneumoniae) with diameters of significant inhibition zones. This study allowed us to evaluate the antibacterial power of the essential oil of Thymus vulgaris in the Nedroma Wilaya region of Tlemcen (Algeria). Therefore, in our study, we observed a decrease in the inhibition diameter proportional to the resistance gradient of the bacteria.
Keywords: Thymus vulgaris; Essential oil; antibacterial activity; Thymus vulgaris; Huile essentielle; activité antibactérienne; الغدة الصعترية الشائع من الضروري النفط; النشاط المضاد للبكتيريا